Fabrication for formamidinium lead bromide perovskite for light emission - Do-Dinh, Khai; Nguyen, Thi Duyen; Phan-Vu, Thi Van; Hoang, Chi Hieu; Truong, Thanh Tu; Nguyen-Tran, Thuat (Communications in Physics, 2024)
Formamidinium bromide was synthesized by slowly mixing formamidinium acetate powder with hydrobromic acid for synthesizing FAPbBr\(_3\). Photoluminescence (PL) of FAPbBr, has been studied, showing a PL peak at 562 nm. Spin-coating method was used to prepare FAPbBr\(_3\) thin films and FTO/FAPbBr/FTO sandwich structures. These structures exhibited green luminescence with a center wavelength at 545 nm. The emission centers were observed for single crystals of FAPbBr\(_3\) perovskite.